Psychosocial Developmental Dynamics of Motherless Child at the industry vs inferiority Stage - Izza Nurhayati; Kharisma Aprilia Ekawati; Novitasari Novitasari; Bambang Pangudiluhur; Indah Lestari (Edukasi, 2026)
The motherless condition refers to a situation in which a child loses or lacks a mother figure during the upbringing process, which has the potential to affect the child’s psychosocial development. This study aims to describe the psychosocial development of elementary school-aged children experiencing a motherless condition based on Erik Erikson’s theory of psychosocial development. This study employs a descriptive qualitative approach using purposive sampling. Data were collected through observation, interviews with teachers and parents, and documentation. Data analysis was conducted descriptively, focusing on the “Industry versus Inferiority” stage of development. The results of the study indicate that: 1) Children living without a mother are still able to demonstrate fairly good psychosocial development; 2) The children exhibit good levels of independence, responsibility, and motivation to learn, although challenges remain in the areas of self-confidence and social relationships; 3) Emotional support from fathers and grandmothers plays a crucial role in helping children adapt to the loss of a mother figure. The study’s findings indicate that the impact of maternal loss on children’s psychosocial development is not solely determined by the mother’s absence but is also influenced by the quality of family support and the social environment experienced by the child.